Acute and repeated dose (28 days) toxicity studies in rats and dogs of recombinant batroxobin, a snake venom thrombin-like enzyme expressed from Pichia pastoris. (April 2017) - Kim, Ok Hwan; Cho, Kil-Sang; Seomun, Young; Kim, Jong-Tak; Chung, Kwang-Hoe
Abstract: Recombinant batroxobin is a thrombin-like enzyme of Bothrops atrox moojeni venom. To evaluate its toxicological effect, it was highly expressed in Pichia pastoris and successfully purified to homogeneity from culture broth supernatant following Good Manufacturing Practice (GMP). The maximum tolerated dose of the recombinant batroxobin was examined in Sprague-Dawley (SD) rat and Beagle dogs following Good Laboratory Practice (GLP) regulations. The approximate lethal dose of recombinant batroxobin was 10 National Institute of Health (NIH) u/kg in male and female rats. Slight test substance-related effects were clearly in male and female dogs at more than 10 NIH u/kg. The maximum tolerated dose (MTD) was considered to be greater than 30 NIH u/kg in dogs. To investigate the repeated dose toxicity of batroxobin, the test item was intravenously administered to groups of SD rat and Beagle dog every day for 4 weeks. We observed that all animals survived the duration of the study without any effects on their mortality. There were no effects in both rats and dogs regarding their clinical signs, body weight, food consumption, ophthalmological examination, urinalysis, hematology, clinical chemistry, organ weightand gross post mortem examinations. The no adverse effect level (NOAEL) of recombinant batroxobin for both males and females is considered to be greater than 2.5 NIH u/kgin rats and 1 NIH u/kg in dogs, respectively. No toxic effects were noted in target organs. In conclusion, these results show a favorable preclinical profile and may contribute clinical development of recombinant batroxobin. Highlights: Recombinant batroxobin was purified from the culture broth of P. pastoris with multi-gram quantity under GMP regulation. Single and 28 days repeated dose toxicity in rats and dogs were examined. Lethal dose, maximum tolerated dose, and no adverse effect level were determined. Clinical signs, hematological parameters, clinical chemistry, and histopathological findings were evaluated.